Sosialisasi Optimalisasi Pangan Lokal untuk Pangan Fungsional di SMP Negeri 5 Ambon - Mainassy, Meillisa Carlen; Seumahu, Cecilia Ana; Birahy, Deford Cristy; Baharudin, Indah; Likumahwa, Christo Putra Yehuda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Local food has great potential as a source of functional food that plays a role in improving health quality and supporting regional food security. However, students' understanding of healthy food and the use of local food is still limited. This community service activity aims to increase the knowledge and awareness of students at SMP Negeri 5 Ambon regarding the optimization of local food as functional food, as well as encourage the formation of positive attitudes towards local food consumption. The methods used included educational and participatory socialization, and evaluation. The results of the activity showed that before the socialization, only about 30% of students were able to explain the concept of healthy food in general and less than 25% knew the function of local food as functional food. After the activity, students' understanding increased, as indicated by approximately 80% of students being able to explain the concept of functional food simply and 75% being able to identify examples of local food that have health benefits. In addition, approximately 70% of students were actively involved in discussions related to daily food consumption habits. This activity is expected to raise students' awareness to utilize local food as a healthy and nutritious alternative.